Bacterial membrane vesicles and phages in blood after consumption of lacticaseibacillus rhamnosus JB-1. (1st January 2021) - Champagne-Jorgensen, Kevin; Jose, Tamina A.; Stanisz, Andrew M.; Mian, M. Firoz; Hynes, Alexander P.; Bienenstock, John
ABSTRACT: Gut microbiota have myriad roles in host physiology, development, and immunity. Though confined to the intestinal lumen by the epithelia, microbes influence distal systems via poorly characterized mechanisms. Recent work has considered the role of extracellular vesicles in interspecies communication, but whether they are involved in systemic microbe-host interaction is unclear. Here, we show that distinctive nanoparticles can be isolated from mouse blood within 2.5 h of consuming Lacticaseibacillus rhamnosus JB-1. In contrast to blood nanoparticles from saline-fed mice, they reproduced lipoteichoic acid-mediated immune functions of the original bacteria, including activation of TLR2 and increased IL-10 expression by dendritic cells. Like the fed bacteria, they also reduced IL-8 induced by TNF in an intestinal epithelial cell line. Though enriched for host neuronal proteins, these isolated nanoparticles also contained proteins and viral (phage) DNA of fed bacterial origin. Our data strongly suggest that oral consumption of live bacteria rapidly leads to circulation of their membrane vesicles and phages and demonstrate a nanoparticulate pathway whereby beneficial bacteria and probiotics may systemically affect their hosts.